LOVE CONFESSIONS IN JAPANESE FROM STREET INTERVIEW - Filia, Filia; Nurfitri, Rizki (UI Scholars Hub, 2020)
This paper examines expressions of love confession in Japanese. Love confession is expressed not only verbally but also nonverbally. Sometimes it needs to be communicated both verbally and nonverbally. It seems the variations of love confession not limited to the common phrases (such as suki desu 'I love you', tsukiatte kudasai 'can we have a relationship?'). In preliminary observation, we found love confession declared not only in common phrases but also in indirect expressions of love confession. This is become a point of departure to overview expression of love confession in Japanese.The data are collected from 12 street interview videos. Street interview videos are used as corpus because those videos are impromptu and no language editing. Based on observations of 79 data of love confessions in Japanese, there are 16 expressions of love confessions. There are expressions of love confession closely related to culural context, such as oishii gohan o tsukutte kudasai 'please make delicious rice for me', ore no kakigori o issho ni tskutte kudasai 'please make shaving ice for me together', kono hanabi no yoo ni, atsui natsu o sugosoo ze 'let's have a hot summer like this firework'. These love confessions have cultural context related to sustainability and togetherness. Sustainability and togetherness are the values of love relationship.